Peran Kepala Sekolah Sebagai Pemimpin Pembelajaran Dalam Implementasi Six Sigma Untuk Peningkatan Mutu Pendidikan: Peran Kepala Sekolah Sebagai Pemimpin Pembelajaran Dalam Implementasi Six Sigma Untuk Peningkatan Mutu Pendidikan - Januar Pandapotan; Juliana Juliana; Jamaluddin Idris (Jurnal Pustaka Cendekia Pendidikan, 2026)
This study aims to explore the role of school principals as instructional leaders in implementing the Six Sigma approach to improve educational quality. A qualitative descriptive method was employed, with data collected through observation, interviews, and documentation. The findings indicate that principals play a crucial role in each stage of the DMAIC (Define, Measure, Analyze, Improve, Control) cycle. The integration of Six Sigma contributes to improving teaching quality, enhancing teacher performance, and strengthening school quality management systems. However, challenges remain in terms of limited resources and the need for a stronger quality culture. Therefore, the integration of instructional leadership and Six Sigma is considered an effective strategy for sustainable educational improvement.